Motivations to engage in word-of-mouth behavior on social network sites. (September 2016) - Luarn, Pin; Huang, Peng; Chiu, Yu-Ping; Chen, I-Jen
The main objective of this study was to enhance the understanding of users' motivation to engage in word-of-mouth behavior on social network sites. This study conducted a hierarchical regression analysis to examine the motivations of social and personal constructs that may influence users' engagement in word-of-mouth. The results posited that not only social constructs (tie strength, expressiveness, social enhancement, relationship management, normative influence, and informational influence), but also personal constructs (altruism, narcissism, image building, and achievement) positively affect users' engagement in word-of-mouth. These findings can provide useful implications for theory in relation to the motives to disseminate word-of-mouth, and be a useful resource and reference for marketing practice.